2001
DOI: 10.1007/s11627-001-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and simple plant regeneration via organogenesis from leaf segment cultures of persimmon (Diospyros kaki thunb.)

Abstract: An efficient and simple plant regeneration system via organogenesis from leaf segments of persimmon (Diospyros kaki Thunb.) cultivars`Fuyu' and`Nishimurawase' has been developed. The regeneration capacity was influenced by the culture vessels, gelling agents, plant growth regulators, and light conditions. Leaf explants taken from in vitro shoots were cultured on a modified Murashige and Skoog medium (MS 1 2 N) for 16 wk without transfer to fresh medium. Adventitious shoots appeared after 4 and 8 wk in culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
5

Year Published

2003
2003
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
1
9
0
5
Order By: Relevance
“…Limited and controversial information is available regarding the effect of dark treatment on plant regeneration. Although there are reports that dark treatment significantly increased plant regeneration of apple, purslane, persimmon, castors, and so on (Ahn et al, 2007;Choi et al, 2001;Fasolo et al, 1989;Fiore et al, 1997;Gu and Zhang, 2005;Rossi-Hassani and Zryd, 1995), other researches showed no stimulatory effect of dark treatment on plant regeneration of Rubus and Juncus accuminatus (Fiola et al, 1990;Sarma and Rogers, 1998). Our other research results on several species, including aspen, birch, chokecherry, periwinkle, and viburnum, showed that the effect of dark was not only species-but also genotype-dependent (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Limited and controversial information is available regarding the effect of dark treatment on plant regeneration. Although there are reports that dark treatment significantly increased plant regeneration of apple, purslane, persimmon, castors, and so on (Ahn et al, 2007;Choi et al, 2001;Fasolo et al, 1989;Fiore et al, 1997;Gu and Zhang, 2005;Rossi-Hassani and Zryd, 1995), other researches showed no stimulatory effect of dark treatment on plant regeneration of Rubus and Juncus accuminatus (Fiola et al, 1990;Sarma and Rogers, 1998). Our other research results on several species, including aspen, birch, chokecherry, periwinkle, and viburnum, showed that the effect of dark was not only species-but also genotype-dependent (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Shoots that developed roots using this method were transplanted to small pots; of the 80 rooted shoots transferred, 60 (75%) plantlets survived in the greenhouse. The induction of roots by the basal dipping of shoots developed in vitro in an IBA solution for short periods and subsequent transfer to growth regulator-free medium has been reported in Diospyros kaki (Choi et al 2001) and Ceratonia siliqua (Romano et al 2002). In the present study, the rooted shoots were transferred directly to the greenhouse following the dipping in auxin solution.…”
Section: Rooting and Transplantationmentioning
confidence: 98%
“…It regenerated as many as 66 shoots per leaf segment (5 mmϫ5 mm), which is more efficient than reported previously (Choi et al 2001). Although it should be examined how frequently somaclonal variation occurs through culture with TDZ, this protocol may be applicable in agricultural practice.…”
mentioning
confidence: 90%